The image of women in Nawal El Saadawi’s novelist’s world - Taha, Maha Mohamed (Journal of Humanities & Social Sciences, 2022)
The purpose of this research was to ascertain the image of women in the universe of author Nawal El-Saadawi. among them. This research accomplished this by including an introduction, a prologue, three chapters, and a conclusion. The preface was written to showcase the feminist novel’s picture of women and to introduce Nawal El Saadawi. As a result, the first chapter, headed "Patterns of the female image in Nawal Al-books," Saadawi’s is separated into two sections: the first discusses the notion of the image and its varieties, and the second discusses women’s patterns. It appeared in the second chapter, named "Features of the interaction between the woman and the other in Nawal Al-books," Saadawi’s as well as the third chapter, titled "Drawing the woman’s character in Nawal Al-novels," Saadawi’s and was separated into: The first subject of discussion is the idea of personality. The second subject is the methods used to depict women in Nawal Al-novels: Saadawi’s the figurative technique, the introspective method, and the declarative way. The study reached many results, perhaps the most important of which is that Nawal El-Saadawi dealt with social, political and national issues, especially issues related to women, Finally, the conclusion, which included the most important findings of the research in terms of results, recommendations and suggestions.